Reaction of Detached Fruits from Selected Cocoa Clones to Artificial Inoculation with Phytophthora Palmivora (Global Journal of Science Frontier Research, 2020)
Black pod rot(BPR) caused by several species of the genus Phytophthora, is one of the most limiting diseases for the production of cocoa as it appears in all of the producing regions of the world and generates significant losses.The aim of this study was to establish the response to infection in six cacao clones, EET8, IMC67, TSH565, PA46, ICS95, and CCN51,through the detached fruits inoculation test using five P. palmivora isolates from five producing regions. The incidence and severity of the disease in the detached pods were evaluated at six and ten days after inoculation (DAI). Clone CCN51 was classified as susceptible, and clones IMC67 and PA46 as moderately susceptible at six DAI. All the clones evaluated were categorized as susceptible at ten DAI. The HURV19 isolates of P. palmivora showed the highest aggressiveness compared to ANYA228, which was found to be the least aggressive.
Keywords: black pod rot; theobroma cacao; genetic resistance